Converting debt into equity in private limited companies in Thailand. Issue 1 (7th December 2020) - Reekie, Adam
Abstract : Purpose: The purpose of this paper is to critically examine the prohibition on debt-to-equity conversions for private limited companies in Thailand, resulting from an interpretation of Section 1119 of the Thai Civil and Commercial Code (TCCC) adopted by academics and the regulator. Design/methodology/approach: This paper critically examines the interpretation of Section 1119 of the TCCC made by academics, the Thai Supreme Court and the regulator. Taking an approach, which draws on debate in the EU over the past two decades, this paper presents a new understanding of the rules relating to legal capital in Thailand. This new understanding is applied to challenge the orthodox interpretation of Section 1119. Findings: The interpretation proposed by this paper is that debt-to-equity conversions may be permitted when viewed as shares issued in return for payment in kind. This proposed interpretation is consistent with existing Thai Supreme Court jurisprudence. In addition, a close reading of the provision, further supported by a historical investigation into the legislative drafting process, reveals that it reflects the original intention behind this provision. Originality/value: This paper presents a view of Thai legal capital rules, which challenges the orthodox understanding of their nature, purpose and categorisation. Furthermore, the proposed interpretation of Section 1119 of the TCCC, if adopted by the regulator, would permit Thai private limited companies to engage in debt-to-equity swaps without further legislative intervention.